Health Related Quality of life of Diabetic and Non-Diabetic Elderly in a Municipality of Central Nepal - Sapkota, Srijana; Poudyal, Jiwan Kumar; Shah, Rajani; Thapa, Kanchan (Journal of College of Medical Sciences-Nepal, 2021)
Background: Quality of life (QoL) is the perception of an individual about their position in life. Chronic diseases such as diabetes are said to have influence on QoL. Health condition changes with increased age and chronic disease condition. This study aimed to assess Health-Related QoL of diabetic and non-diabetic elderly. Method: A community based cross-sectional study was conducted among 167 elderly in Gaindakot municipality of Nawalpur, Nepal. Health related QoL was assessed using World Health Organization QoL Instrument scale. Data was analyzed using descriptive as well as inferential statistics. Results: Among the diabetic respondents, highest mean score was obtained in social relationship (68.76), whereas environmental health (69.02) holds highest mean score among non-diabetic. Non-diabetics were in better position in terms of both psychological (63.23 vs 55.77) and physical health (62.23 vs 57.15) than diabetics. Overall QoL and overall health perception were found to be significantly correlated with all domains of QoL at (p<0.05) and (p<0.01) respectively among diabetics. Age group, gender, educational status, marital status and employment status were found to be statistically associated with different domains of QoL in both groups but caste, family type smoking and alcohol intake didn’t show any association with any of the domain of QoL in both groups. Conclusion: Three domains of Health Related QoL (physical, psychological and environmental health) except social relationship were better among non-diabetic compared to that of diabetic respondents. Preventing diabetes and focusing on physical, psychological and environmental health of diabetics are required for a healthy elderly life.